Analisis Keuntungan Usaha Mie Basah Ud. Aneke Dalam Masa Pandemi Covid-19 Di Manado - Oktafiani Elisa Hogeh; Ribka Magdalena Kumaat; Celcius Talumingan (Sam Ratulangi University, 2022)
This study aims to determine the profit of analysis of UD. Aneke’s wet noodle business during the Covid-19 pandemic in Manado. This research was carried out during July and December 2021 at UD. Aneke which is in the Karisma Ranomuut Housing. The data used in this study are primary and secondary data. Primary data was obtained through direct interviews with business owners from UD. Aneke by using a list of question (questionnaire). Meanwhile, secondary data were taken from agencies related to this research. The data collected is then analyzed using profit analysis by calculating the difference between revenue and costs used then followed by the Cost Ratio (R/C) analysis formula. This results of this study indicate that the UD. Aneke wet noodle business is profitable. Profit in July 2021 is Rp 6.690.892 with an R/C ratio of 1,22 and a profit in December 2021 of Rp 11.340.891 with an R/C value of 1,35.